Preparation method of photo-thermal energy storage thermally induced flexible phase change hydrogel

By constructing a ternary composite system of "gel-sodium acetate trihydrate-carbonized wood powder", the problem that existing phase change materials cannot efficiently collect and store solar energy, and the efficient conversion of solar energy and reversible storage of thermal energy are achieved. The material has the characteristics of thermal flexibility and is suitable for applications in multiple fields.

CN120137094APending Publication Date: 2025-06-13NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510507416.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Existing phase change materials cannot achieve soft and hard switching and efficient collection and long-term storage of solar energy.

Method used

The "gel-sodium acetate trihydrate-carbonized wood powder" ternary composite system is adopted to improve the photothermal conversion performance by carbonized wood powder as a photothermal agent. Sodium acetate trihydrate reversibly stores and releases a large amount of latent heat through crystallization-melt transformation to achieve thermal flexibility.

Benefits of technology

It realizes the efficient conversion of solar energy to thermal energy and the reversible storage of thermal energy. The material has changed from hard and brittle to soft and soft, which is in line with the concept of sustainable science and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137094A_ABST
    Figure CN120137094A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of photo-thermal energy storage thermally induced flexible phase change hydrogel, and belongs to the field of phase change materials. The invention aims to solve the problem that the existing phase change material cannot realize soft and hard switching and efficient collection and long-term storage of solar energy. The method comprises the following steps: 1, preparing carbonized wood powder; 2, heating and melting sodium acetate trihydrate; and 3, thermally initiated polymerization. The preparation method is used for preparing the photo-thermal energy storage thermally induced flexible phase change hydrogel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of phase change materials. Background Art

[0002] In recent years, global energy consumption has been continuously rising, and the transformation of the energy structure is imminent. Among many renewable energy sources, solar energy has become a research hotspot in the energy field due to its significant advantages such as universality, permanence, cleanliness, and safety. However, the intermittent and unstable problems of solar energy severely restrict its large-scale application. To address this challenge, phase change materials (PCMs), as an efficient thermal energy storage medium, have gradually become a research hotspot due to their high energy storage density and nearly constant-temperature phase change characteristics.

[0003] However, due to reasons such as weak sunlight absorption ability and poor structural stability of existing phase change materials, it is impossible to achieve soft-hard switching and efficient collection and long-term storage of solar energy. Summary of the Invention

[0004] The present invention aims to solve the problems that existing phase change materials cannot achieve soft-hard switching and efficient collection and long-term storage of solar energy, and further provides a preparation method of a photothermal energy storage thermally induced flexible phase change hydrogel.

[0005] A preparation method of a photothermal energy storage thermally induced flexible phase change hydrogel is carried out according to the following steps:

[0006] I. Preparation of carbonized wood powder:

[0007] The wood is crushed into wood powder and dried, and then the dried wood powder is carbonized under the condition of a temperature of 800 °C to 1400 °C to obtain carbonized wood powder;

[0008] II. Heating and melting of sodium acetate trihydrate:

[0009] Sodium acetate trihydrate and ethylene glycol are added to water and heated until sodium acetate trihydrate melts to obtain a mixture;

[0010] III. Thermal initiation polymerization:

[0011] Under the conditions of stirring and a temperature of 70 °C to 80 °C, acrylamide monomer, N,N'-methylenebisacrylamide, and carbonized wood powder are added to the mixture. After stirring evenly and cooling to 40 °C to 45 °C, ammonium persulfate is added and stirred and mixed evenly, and then poured into a mold for thermal initiation polymerization to obtain the photothermal energy storage thermally induced flexible phase change hydrogel.

[0012] The beneficial effects of the present invention are:

[0013] Based on the technical requirements of efficient solar energy collection and storage, the present invention innovatively constructs a ternary composite system of "gel-sodium acetate trihydrate-carbonized wood powder", and successfully prepares a photothermal energy storage thermally induced flexible phase change hydrogel. Among them, the carbonized wood powder, as a photothermal agent, significantly improves the photothermal conversion performance. Sodium acetate trihydrate, as a phase change material, reversibly stores and releases a large amount of latent heat through the crystallization-melting transition and provides thermal induced flexibility, enabling the photothermal phase change hydrogel to transform from hard and brittle to soft and flexible. Experimental results show that under the illumination of a 300UV xenon lamp, the hydrogel can rapidly heat up to 84.7 °C within 500 s, achieving efficient conversion of solar energy into thermal energy. At the same time, the phase change material reversibly stores the thermal energy in the form of crystallization-melting.

[0014] This material conforms to the concept of sustainable science, provides a new solution for the storage and utilization of renewable energy, and helps to promote the transformation of the energy structure and environmental protection. At the same time, the flexible characteristics of this material also show broad application prospects in the fields of human thermal management, thermal control of electronic devices, and medical treatment. Brief Description of the Drawings

[0015] Figure 1 It is the preparation flow chart of the photothermal energy storage thermally induced flexible phase change hydrogel in Example 1;

[0016] Figure 2 It is the physical picture of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Example 2;

[0017] Figure 3 It is the optical microscope image of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Example 2. a) shows the material in the molten state, and b) shows the material in the crystalline state;

[0018] Figure 4 It is the scanning electron microscope image of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Examples 1, 3 and 4 in the crystalline state and the carbonized wood powder prepared in Step 1 of Example 1. a) is Example 1, b) is Example 3, c) is Example 4, and d) is the carbonized wood powder;

[0019] Figure 5 It is the XRD pattern of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Examples 1 to 4 and the comparative experiment, the carbonized wood powder prepared in Step 1 of Example 1, and sodium acetate trihydrate;

[0020] Figure 6 It is the light reflectance of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Examples 1 to 4 and the comparative experiment measured by an ultraviolet-visible spectrophotometer in the crystalline state in the wavelength range of 200 nm - 860 nm;

[0021] Figure 7Tensile stress-strain curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 and the comparative experiment in the crystalline state;

[0022] Figure 8 Compressive stress-strain curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 and the comparative experiment in the crystalline state;

[0023] Figure 9 Flexibility display diagram of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Example 2 in the molten state;

[0024] Figure 10 Thermally induced flexibility comparative display diagram of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Example 2;

[0025] Figure 11 Infrared imaging diagrams of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 and 4 under 300 UV xenon lamp illumination;

[0026] Figure 12 Temperature-time curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 under 300 UV xenon lamp illumination;

[0027] Figure 13 Melting curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 and the comparative experiment and sodium acetate trihydrate measured by differential scanning calorimeter (DSC). Detailed implementation manners

[0028] Detailed implementation manner 1: This implementation manner is a preparation method of a photothermal energy storage thermally induced flexible phase change hydrogel, and it is carried out according to the following steps:

[0029] I. Preparation of carbonized wood powder:

[0030] The wood is crushed into wood powder and dried, and then the dried wood powder is carbonized at a temperature of 800 °C to 1400 °C to obtain carbonized wood powder;

[0031] II. Heating and melting of sodium acetate trihydrate:

[0032] Sodium acetate trihydrate and ethylene glycol are added to water and heated until sodium acetate trihydrate melts to obtain a mixture;

[0033] III. Thermal initiation polymerization:

[0034] Under the conditions of stirring and a temperature of 70 °C to 80 °C, acrylamide monomer, N,N'-methylenebisacrylamide, and carbonized wood powder are added to the mixture. After stirring evenly and cooling to 40 °C to 45 °C, ammonium persulfate is added and stirred to mix evenly, and then poured into a mold for thermal initiation polymerization to obtain a photothermal energy storage thermally induced flexible phase change hydrogel.

[0035] The beneficial effects of this embodiment are:

[0036] Based on the technical requirements of efficient solar energy collection and storage, this embodiment innovatively constructs a ternary composite system of "gel-sodium acetate trihydrate-carbonized wood powder" and successfully prepares a photothermal energy storage thermally induced flexible phase change hydrogel. Among them, carbonized wood powder, as a photothermal agent, significantly improves the photothermal conversion performance. Sodium acetate trihydrate, as a phase change material, reversibly stores and releases a large amount of latent heat through the crystallization-melting transition and provides thermal-induced flexibility, enabling the photothermal phase change hydrogel to achieve a transformation from hard and brittle to soft and flexible. Experimental results show that under the illumination of a 300UV xenon lamp, the hydrogel can rapidly heat up to 84.7 °C within 500 s, realizing the efficient conversion of solar energy into thermal energy. At the same time, the phase change material reversibly stores the thermal energy in the form of crystallization-melting.

[0037] This material conforms to the concept of sustainable science, provides a new solution for the storage and utilization of renewable energy, and helps to promote the transformation of the energy structure and environmental protection. At the same time, the flexible characteristics of this material also show broad application prospects in the fields of human thermal management, thermal control of electronic devices, and medical treatment.

[0038] Specific Embodiment 2: The difference between this embodiment and Specific Embodiment 1 is that the particle size of the wood powder described in Step 1 is 75 μm to 85 μm. Others are the same as Specific Embodiment 1.

[0039] Specific Embodiment 3: The difference between this embodiment and either Specific Embodiment 1 or 2 is that the drying in Step 1 is specifically carried out under the condition of a temperature of 50 °C to 80 °C until the moisture content of the wood powder is lower than 10%. Others are the same as Specific Embodiment 1 or 2.

[0040] Specific Embodiment 4: The difference between this embodiment and any one of Specific Embodiments 1 to 3 is that in Step 1, the dried wood powder is carbonized at a temperature of 300 °C to 600 °C for 3 h to 5 h. Others are the same as Specific Embodiments 1 to 3.

[0041] Specific Embodiment 5: The difference between this embodiment and any one of Specific Embodiments 1 to 4 is that the mass ratio of sodium acetate trihydrate to ethylene glycol in Step 2 is 1:(0.02 - 0.03); the mass ratio of sodium acetate trihydrate to water in Step 2 is 1:(0.02 - 0.03). Others are the same as Specific Embodiments 1 to 4.

[0042] Embodiment Six: The difference between this embodiment and any one of Embodiments One to Five is that in Step 2, it is heated at a temperature of 70°C to 80°C for 1.5 h to 2 h until sodium acetate trihydrate melts. Others are the same as those in Embodiments One to Five.

[0043] Embodiment Seven: The difference between this embodiment and any one of Embodiments One to Six is that in Step 2, the mass ratio of acrylamide monomer to N,N - methylenebisacrylamide is 1:(0.01 - 0.02); the mass ratio of acrylamide monomer to carbonized wood powder is 1:(0.03 - 0.15); the mass ratio of acrylamide monomer to the mixture is 1:(6.00 - 6.20). Others are the same as those in Embodiments One to Six.

[0044] Embodiment Eight: The difference between this embodiment and any one of Embodiments One to Seven is that in Step 2, the mass ratio of acrylamide monomer to ammonium persulfate is 1:(0.03 - 0.04). Others are the same as those in Embodiments One to Seven.

[0045] Embodiment Nine: The difference between this embodiment and any one of Embodiments One to Eight is that in Step 3, it is poured into a mold and covered with a plastic wrap, and then thermally initiated polymerization is carried out at a temperature of 60°C to 80°C for 2 min to 3 min. Others are the same as those in Embodiments One to Eight.

[0046] Embodiment Ten: The difference between this embodiment and any one of Embodiments One to Nine is that the stirring speed in Step 3 is 600 r / min to 900 r / min. Others are the same as those in Embodiments One to Nine.

[0047] The following examples are used to verify the beneficial effects of the present invention:

[0048] Example One, combined with Figure 1 Specific description:

[0049] A preparation method of a photothermal energy storage thermally induced flexible phase change hydrogel, which is carried out according to the following steps:

[0050] I. Preparation of carbonized wood powder:

[0051] The wood is crushed into wood powder, and dried at a temperature of 80°C until the moisture content of the wood powder is 8%, and then the dried wood powder is carbonized at a temperature of 800°C for 3 h to obtain carbonized wood powder;

[0052] II. Heating and melting of sodium acetate trihydrate:

[0053] Add 22 g of sodium acetate trihydrate (SAT), 0.6 g of ethylene glycol to 0.6 g of water, and heat at 80 °C for 1.5 h. The sodium acetate trihydrate melts to obtain a mixture.

[0054] III. Thermal initiation polymerization:

[0055] Under the conditions of a stirring speed of 800 r / min and a temperature of 75 °C, add 3.8 g of acrylamide monomer (AM), 0.04 g of N,N'-methylenebisacrylamide (MBA), and 0.14 g of carbonized wood powder to 23.2 g of the mixture. After stirring evenly and cooling to 40 °C, add 0.12 g of ammonium persulfate (APS), and stir and mix evenly under the condition of a stirring speed of 800 r / min. Then pour it into a mold and cover it with plastic wrap, and carry out thermal initiation polymerization at 60 °C for 3 min to obtain a photothermal energy storage and thermally induced flexible phase change hydrogel.

[0056] The average particle size of the wood powder described in Step I is 80 μm.

[0057] Example 2: The difference between this example and Example 1 is that the addition amount of carbonized wood powder in Step III is 0.27 g. Others are the same as in Example 1.

[0058] Example 3: The difference between this example and Example 1 is that the addition amount of carbonized wood powder in Step III is 0.41 g. Others are the same as in Example 1.

[0059] Example 4: The difference between this example and Example 1 is that the addition amount of carbonized wood powder in Step III is 0.54 g. Others are the same as in Example 1.

[0060] Comparative experiment: The difference between this comparative experiment and Example 1 is that the addition of carbonized wood powder in Step III is omitted. Others are the same as in Example 1.

[0061] Calculate the mass fraction of carbonized wood powder = mass of carbonized wood powder / (mass of sodium acetate trihydrate + mass of ethylene glycol + mass of water + mass of AM + mass of MBA + mass of APS) × 100%. The mass fractions of carbonized wood powder in the photothermal energy storage and thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 are 0.5 wt%, 1 wt%, 1.5 wt%, and 2 wt% respectively; then the mass fraction of carbonized wood powder in the photothermal energy storage and thermally induced flexible phase change hydrogel prepared in the comparative experiment is 0 wt%.

[0062] Figure 2 It is a physical picture of the photothermal energy storage and thermally induced flexible phase change hydrogel prepared in Example 2. As can be seen from the figure, the photothermal phase change hydrogel under normal temperature and pressure is in a crystalline state, has a certain hardness, and can bear a 100 g weight.

[0063] Figure 3Optical microscope images of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Example 2. a) shows the material in the molten state, and b) shows the material in the crystalline state. By comparing a) and b), the surface morphology differences of the photothermal phase change hydrogel in the crystalline state and the molten state (heated at 80 °C for 60 min) can be observed. The crystal distribution can be clearly seen in the crystalline state, while the molten state shows a relatively smooth feature.

[0064] Figure 4 Scanning electron microscope images of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1, 3, and 4 in the crystalline state and the carbonized wood powder prepared in Step 1 of Example 1. a) is Example 1, b) is Example 3, c) is Example 4, and d) is the carbonized wood powder. As can be seen from the figure, the carbonized wood powder particles are dispersed in the three-dimensional network structure of the hydrogel. As a reinforcing body, it can improve the mechanical properties of the hydrogel. The carbonized wood powder presents a rod-like or long strip-like morphology, and there are obvious grooves on the surface.

[0065] Figure 5 XRD patterns of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 and the comparative experiment, the carbonized wood powder prepared in Step 1 of Example 1, and sodium acetate trihydrate. As shown in the figure, SAT has two main diffraction peaks at 11.4° and 16.9°, corresponding to the crystal planes (110) and (020) respectively; the XRD diffraction peaks of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 and the comparative experiment are mainly located at 8.9°, 11.4°, 16.9°, 22.3°, 26.8°, and 35.5°. When the carbonized wood powder and sodium acetate trihydrate are added to the gel matrix, the main diffraction peaks of the carbonized wood powder and sodium acetate trihydrate appear on the prepared photothermal phase change hydrogel, indicating that the carbonized wood powder and sodium acetate trihydrate are successfully distributed into the three-dimensional network structure of the gel.

[0066] Figure 6 The light reflectance of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 and the comparative experiment in the crystalline state measured by an ultraviolet-visible spectrophotometer in the wavelength range of 200 nm - 860 nm. As can be seen from the figure, with the increase in the content of the carbonized wood powder, the light reflectance of the photothermal phase change hydrogel gradually decreases, which also indirectly indicates that the addition of the carbonized wood powder makes the light absorption ability of the gel gradually increase.

[0067] Figure 7Tensile stress-strain curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared for Examples 1 to 4 and the comparative experiment in the crystalline state. As can be seen from the figure, with the addition of carbonized wood powder, the fracture strength of the hydrogel gradually increases, indicating that the addition of carbonized wood powder improves the mechanical properties of the hydrogel. The elastic modulus increases from 54.67 MPa (comparative experiment) to 758.46 MPa (Example 4), and the tensile strength increases from 5.36 MPa (comparative experiment) to 8.43 MPa (Example 4).

[0068] Figure 8 Compressive stress-strain curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared for Examples 1 to 4 and the comparative experiment in the crystalline state. As can be seen from the figure, with the addition of carbonized wood powder, the compressive strength of the hydrogel gradually increases, indicating that the addition of carbonized wood powder improves the mechanical properties of the hydrogel. The elastic modulus increases from 10.83 MPa (comparative experiment) to 72.39 MPa (Example 4), and the compressive strength increases from 5.12 MPa (comparative experiment) to 5.84 MPa (Example 4).

[0069] Figure 9 Flexibility display diagram of the photothermal energy storage thermally induced flexible phase change hydrogel prepared for Example 2 in the molten state. As can be seen from the figure, the photothermal phase change hydrogel in the molten state (heated at 80 °C for 60 min) has good flexibility and can be folded into any shape.

[0070] Figure 10 Thermally induced flexibility comparative display diagram of the photothermal energy storage thermally induced flexible phase change hydrogel prepared for Example 2. As can be seen from the figure, as the temperature increases, sodium acetate trihydrate changes from the crystalline state (25 °C) to the molten state (heated at 80 °C for 60 min), resulting in a change of the photothermal phase change hydrogel from hard and brittle to soft and flexible, demonstrating the thermally induced flexibility characteristic of the photothermal phase change hydrogel.

[0071] Figure 11 Infrared imaging diagrams of the photothermal energy storage thermally induced flexible phase change hydrogels prepared for Examples 1 and 4 under 300 UV xenon lamp illumination. Comparing the photothermal energy storage thermally induced flexible phase change hydrogels prepared for Examples 1 and 4, it is found that the photothermal energy storage thermally induced flexible phase change hydrogel prepared for Example 4 shows higher thermal imaging brightness and temperature at 400 s, indicating that increasing the carbonized wood powder content can improve the photothermal conversion performance of the material.

[0072] Figure 12Temperature-time curves of the photothermal energy storage thermally induced flexible phase change hydrogels prepared in Examples 1 to 4 under 300 UV xenon lamp irradiation. As can be seen from the figure, the temperatures of all samples gradually increased under the irradiation of the 300 UV xenon lamp. The temperature-time curve of the photothermal energy storage thermally induced flexible phase change hydrogel prepared in Example 4 had the largest rising slope at the initial stage of heating, and the final temperature reached 84.7 °C, indicating that the addition of carbonized wood powder enhanced the photothermal conversion performance of the photothermal phase change material.

[0073] Figure 13 Melting curves of the photothermal energy storage thermally induced flexible phase change hydrogels and sodium acetate trihydrate prepared in Examples 1 to 4 and the comparative experiment measured by a differential scanning calorimeter (DSC). As Figure 13 shown in Table 1, there was an obvious endothermic peak during heating (the phase change temperatures and phase change enthalpies of different samples are detailed in Table 1). The introduction of carbonized wood powder led to significant changes in the enthalpy change (ΔH) and phase change temperature. As the addition amount of carbonized wood powder gradually increased, the phase change temperature decreased from 56.94 °C to 48.10 °C, confirming that the addition of carbonized wood powder reconstructed the phase change thermodynamic behavior by affecting the internal energy distribution of the hydrogel.

[0074] Table 1

[0075]

Claims

1. A method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel, characterized in that It is carried out in the following steps:

1. Preparation of carbonized wood powder: The wood is crushed into wood powder and dried, and then the dried wood powder is carbonized at a temperature of 800°C to 1400°C to obtain carbonized wood powder; Heating and melting of sodium acetate dihydrate and trihydrate: Adding sodium acetate trihydrate and ethylene glycol into water, and heating until the sodium acetate trihydrate is melted, to obtain a mixture; 3. Thermally initiated polymerization: Under stirring conditions at a temperature of 70°C to 80°C, acrylamide monomer, N,N-methylenebisacrylamide and carbonized wood powder are added to the mixture. After being stirred evenly and cooled to 40°C to 45°C, ammonium persulfate is added and stirred to mix evenly. The mixture is then poured into a mold to initiate thermal polymerization to obtain a photothermal energy storage thermo-induced flexible phase change hydrogel.

2. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that The particle size of the wood powder described in step 1 is 75 μm to 85 μm.

3. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that The drying in step 1 is specifically drying at a temperature of 50° C. to 80° C. until the moisture content of the wood powder is less than 10%.

4. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that In step 1, the dried wood powder is carbonized at a temperature of 300° C. to 600° C. for 3 h to 5 h.

5. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that The mass ratio of sodium acetate trihydrate to ethylene glycol described in step 2 is 1:(0.02-0.03); the mass ratio of sodium acetate trihydrate to water described in step 2 is 1:(0.02-0.03).

6. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that In step 2, the sodium acetate trihydrate is heated at 70° C. to 80° C. for 1.5 to 2 hours until it melts.

7. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that The mass ratio of the acrylamide monomer described in step 2 to N,N-methylenebisacrylamide is 1:(0.01-0.02); the mass ratio of the acrylamide monomer described in step 2 to carbonized wood powder is 1:(0.03-0.15); the mass ratio of the acrylamide monomer described in step 2 to the mixture is 1:(6.00-6.20).

8. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that The mass ratio of acrylamide monomer to ammonium persulfate in step 2 is 1:(0.03-0.04).

9. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that In step 3, the mixture is poured into a mold and covered with plastic wrap, and then thermally initiated polymerization is performed at a temperature of 60° C. to 80° C. for 2 min to 3 min.

10. The method for preparing a photothermal energy storage thermo-induced flexible phase change hydrogel according to claim 1, characterized in that The stirring speed described in step 3 is 600r / min~900r / min.